Exploring the mechanism of sesamin for the treatment of PM2.5-induced cardiomyocyte damage based on transcriptomics, network pharmacology and experimental verification - Zhang, Yadong; Wen, Rui; Ren, Jingyi; Zhang, Fan; Pei, Huanting; Zuo, Jinshi; Ma, Yuxia (Frontiers in Pharmacology, 2024)
Exposure to fine particulate matter (PM2.5) is known to be associated with cardiovascular diseases. Sesamin (Ses) is a natural phenolic compound found in sesame seeds and sesame oil. Ferroptosis is a novel mode of cell death characterised by iron-dependent lipid peroxidation. This study aims to explore whether PM2.5 can induce ferroptosis in H9C2 cells and to investigate the precise protective mechanism of Ses. Based on transcriptomic data, PM2.5 may induce ferroptosis in cardiomyocytes. The ferroptosis inducer erastin and ferroptosis inhibitor ferrostatin-1 (Fer-1) were used to illustrate the mechanisms involved in PM2.5-induced H9C2 cell injury. Using network pharmacology, the pharmacological mechanism and potential therapy targets of Ses were explored for the treatment of PM2.5-induced cardiomyocyte injury. H9C2 cells were cultured and pretreated with Fer-1 or different concentrations of Ses, and then cardiomyocyte injury model was established using erastin or PM2.5. Indicators of oxidative responses, including total superoxide dismutase, reduced glutathione, glutathione peroxidase and malondialdehyde, were measured. The expression levels of ferroptosis-related proteins were determined through Western blot analysis. Results demonstrate that PM2.5 induces ferroptosis in H9C2 cells and Ses exerts a protective effect by suppressing ACSL4-mediated ferroptosis. Overall, these findings elucidate a novel mechanism by which Ses ameliorates the detrimental effects of PM2.5 on cardiomyocytes.